Multifunctional Ferroelectric Materials - Ranjan Sahu, Dipti (IntechOpen, 2021)
Ferroelectricity is a well-known phenomenon commonly used in scientific and industrial communities. Ferroelectric materials are the building blocks of different devices and technological innovations. This book presents an overview of the basic phenomenon of ferroelectricity and different ferroelectrics and ferroelectric devices, including their theoretical study, synthesis, characterization, and application. Chapters cover such topics as the basics of ferroelectricity, perovskite ferroelectrics and relaxor ferroelectrics, piezoelectricity, and more.